1985
DOI: 10.1152/ajpgi.1985.249.1.g137
|View full text |Cite
|
Sign up to set email alerts
|

Nonprotein sulfhydryl compounds in canine gastric mucosa: effects of PGE2 and ethanol

Abstract: By use of an in vivo canine chambered stomach preparation in which the gastric mucosa was partitioned into two equal halves, the effect of topical 16,16-dimethyl PGE2 (DMPGE2) (1 microgram/ml of perfusate) and 8% and 40% ethanol on tissue levels of nonprotein sulfhydryl compounds was assessed. Both DMPGE2 and 8% ethanol significantly increased (P less than 0.005) mucosal levels of nonprotein sulfhydryls when compared with corresponding mucosa bathed with saline alone. In contrast, mucosa bathed with 40% ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
19
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
5
19
0
Order By: Relevance
“…In NEM pretreated animals treated with AML, there were a significant increased in the mean score of blood congestion and necrosis when compared with saline pretreated group treated with AML. This is in agreement with a few studies which have been reported previously that ethanol-induced gastric lesions will lead to decrease of sulfhydryl compounds in the gastric mucosa (Szabo et al, 1981;Miller et al, 1985 ;Tariq & Aqeel, 1990 Therefore, from the current histology result in ethanol-induced gastric mucosal lesion treated with AML in NEM-pretreated rats, there was significant increment of certain inflammatory features, indicating the worsening of the ulcer when compared with the group treated with AML in saline pretreated group. Indeed, this indicates a strong involvement of SHs pathway in gastroprotection of AML (Figure 4a) which also in agreement with the result of macroscopic done previously.…”
Section: Discussionsupporting
confidence: 92%
“…In NEM pretreated animals treated with AML, there were a significant increased in the mean score of blood congestion and necrosis when compared with saline pretreated group treated with AML. This is in agreement with a few studies which have been reported previously that ethanol-induced gastric lesions will lead to decrease of sulfhydryl compounds in the gastric mucosa (Szabo et al, 1981;Miller et al, 1985 ;Tariq & Aqeel, 1990 Therefore, from the current histology result in ethanol-induced gastric mucosal lesion treated with AML in NEM-pretreated rats, there was significant increment of certain inflammatory features, indicating the worsening of the ulcer when compared with the group treated with AML in saline pretreated group. Indeed, this indicates a strong involvement of SHs pathway in gastroprotection of AML (Figure 4a) which also in agreement with the result of macroscopic done previously.…”
Section: Discussionsupporting
confidence: 92%
“…This increase in the gastric mucosal LPO concentration with the development of gastric mucosal lesions induced by WIR stress was similar to that shown by Yoshikawa et al [4] and Itoh et al [9]. It has been dem onstrated that SH compounds in the stomach might be important for the maintenance of gastric mucosal integri ty [35][36][37][38] and that about 95% of NP-SH in the stomach is GSH which functions as a scavenger of H^O; and/or lipid hydroperoxides via GSH-px in cells [39], In rats with WIR stress over a 6-hour period, the gastric mucosal NP-SH concentration decreased to about half the level of con trol rats without WIR stress at an early stage of the lesion, i.e" 3 h after the onset of WIR, and a further decrease in that concentration scarcely occurred at a progressed stage of the lesion, i.e., 6 h after the onset of WIR (table 1; fig. 1).…”
Section: Discussionsupporting
confidence: 86%
“…Szabo et al (16), Ezer (17) and Miller et al (18) proposed that sulfhydryl compounds in the gastric mucosa play an important role on the cytoprotection seen with several agents. However, there are controversial data about the role of sulfhydryl compounds (mainly reduced glutathione) in the role of gastric cytoprotection.…”
Section: Discussionmentioning
confidence: 99%